Athletic performance of swimmers after altitude training (2,300 m above sea level) in view of their blood morphology changes - Siewierski, M.; Slominski, P.; Bialecki, R.; Adamczyk, J. (Biology of Sport, 2012)
The aim of the study was to estimate changes in blood morphology caused by participation of record-seeking swimmers in a high altitude training camp at 2,300 m above sea level and to assess their performance during major competitions before and after the camp. Eight swimmers (two females and six males) - record-holders and medallists of the Polish National Championships, as well as finalists and medallists of the European and World Championships and the Olympic Games (including a two-time holder of the world record) - were recruited. During the 2006/2007 season the athletes attended a training camp organized according to the principle "live high and train high". The camp lasted 23 days and consisted of three micro-cycles of training, each of them with specific training objectives. Before and after participation in the training camp erythrocyte (red blood cells; RBC) count, haemoglobin (Hb) concentration and haematocrit (Hct) were estimated at a hospital laboratory. Scores amassed by the examined athletes during major competitions were presented after their transformation into points based on the FINA (International Swimming Federation) tables for years 2005-2008. The best results (time for a distance) achieved during competitions organized before and after participation in the camp were regarded as reference points. Additionally, liquid balance of the body was monitored during 30 selected training units (15 in the morning and 15 in the evening). The response of the examined swimmers from the Polish Olympic Team to the high altitude training (at 2,300 m above sea level) was represented by an almost three-fold increase in blood reticulocyte count during the first micro-cycle of training as well as by an elevated erythrocyte count (by 14.4%), and haemoglobin (by 13.5%) and haematocrit (by 14.8%) levels estimated after completion of the training, as compared to the results obtained before the camp. Six out of eight subjects improved their performance in major competitions organized after the training camp, and four of them broke their personal bests.